Improving Student's Learning Outcomes In Ips Sub Themes Location And Area Of Indonesia Through Map Media In Class VII-A SMPN 1 Rambah Samo - Abduh Abduh (STKIP Rokania Pasir Pangaraian, 2021)
This study aims to improve the social studies learning achievement of grade VII-B students of SMP Negeri 1 Rambah Samo by using Map Media. This type of research is Classroom Action Research (CAR), with the research subjects being students of class VII-B SMP Negeri 1 Rambah Samo, totaling 33 students, namely 18 male students and 15 female students. The design of this study uses the research model of Kemmis and Mc. Taggart. Collecting data using the method of observation (observation) and tests. The data analysis technique used is descriptive quantitative. Based on the results of the study, it can be concluded that by applying Map Media, it can improve the learning achievement of class VII-B students of SMP Negeri 1 Rambah Samo, Rokan Hulu Regency, especially on the subject of Location and Area of ​​Indonesia. There was an increase in the percentage of student learning completeness from the pre-cycle to the first cycle to the first meeting of 24.24%. The results of the evaluation of the first meeting, from 33 students there were 25 students (75.75%) who managed to reach the KKM with an average grade of 68.18. After the action was taken. At the second meeting, 29 students (87.87%) had achieved mastery learning with a class average of 71.81. Followed by cycle II meeting III the number of students who experienced completeness were 31 students with the percentage of completeness was 93.93% with an average value of 74.24. At the fourth meeting, all students were 100% complete